Family integration in pulmonary rehabilitation programmes: A pilot study - Marques, Alda (2013)
Chronic Obstructive Pulmonary Disease (COPD) places a high burden on patients and their family. The World Health Organization has recommended family integration in rehabilitation interventions. However, Pulmonary Rehabilitation (PR) programmes for COPD typically focus on patients, neglecting the family. This study aimed to explore the needs and expectations of patients with COPD and respective family carers and assess their perspectives about their participation in a PR programme. Nine patients with COPD (70±8yrs; FEV169±25%pred) and their family carers (64±11yrs) were recruited in primary care. Individual interviews were conducted to explore their needs and expectations about PR programmes. Focus groups were conducted after their participation in a PR programme. Data were audio-recorded, transcribed and submitted to content analysis. Patients and carers identified the need for more information about COPD (nP=7; nC=5) and emotional support (nP=2; nC=3), and expected PR programmes to improve their skills to manage the disease (nP=9; nC=2). A PR programme with psychoeducation and exercise training was implemented, considering these findings. Participants reported that the programme helped them to cope better with the disease and patients found their carers to be less worried and living happier (n=3). The majority of carers reported self-benefits (n=6) and stressed the importance of on-going support to help themselves and their care receivers (n=2). PR programmes inclusive of carers have the potential to enhance the skills of the whole family to manage COPD and, therefore, to promote a healthy adjustment to the disease. Future research should explore the impact of PR programmes within the family unit.